Intrinsically photosensitive retinal ganglion cells in glaucoma - Gao, Jingyi; Provencio, Ignacio; Liu, Xiaorong (Frontiers in Cellular Neuroscience, 2022)
Glaucoma is a group of eye diseases afflicting more than 70 million people worldwide. It is characterized by damage to retinal ganglion cells (RGCs) that ultimately leads to the death of the cells and vision loss. The diversity of RGC types has been appreciated for decades, and studies, including ours, have shown that RGCs degenerate and die in a type-specific manner in rodent models of glaucoma. The type-specific loss of RGCs results in differential damage to visual and non-visual functions. One type of RGC, the intrinsically photosensitive retinal ganglion cell (ipRGC), expressing the photopigment melanopsin, serves a broad array of non-visual responses to light. Since its discovery, six subtypes of ipRGC have been described, each contributing to various image-forming and nonimage-forming functions such as circadian photoentrainment, the pupillary light reflex, the photic control of mood and sleep, and visual contrast sensitivity. We recently demonstrated a link between type-specific ipRGC survival and behavioral deficits in a mouse model of chronic ocular hypertension. This review focuses on the type-specific ipRGC degeneration and associated behavioral changes in animal models and glaucoma patients. A better understanding of how glaucomatous insult impacts the ipRGC-based circuits will have broad impacts on improving the treatment of glaucoma-associated non-visual disorders.